Genetic diversity of 15 autosomal STRs in a sample of Berbers from Aurès region in the Northeast of Algeria and genetic relationships with other neighbouring samples - Amine Abdeli; Traki Benhassine (Taylor & Francis Group, 2020)
Background: The history of the Aurès mountains and neighbouring areas, a large region of the East of Algeria, was part of the history of the ancient independent Berber kingdoms supposed to be the ancestors of the current Berber people. The genetic background of this region has not yet been clarified. Aim: The aims of our study were to investigate the genetic characteristics of 15 autosomal short tandem repeats (STRs) in a sample from these regions, to determine the degree of heterogeneity among Algerian and North African samples and to analyse the genetic relationships with other populations. Subjects and methods: Allele frequencies, forensic parameters and Hardy-Weinberg equilibrium (HWE) of 15 autosomal STRs included in the PowerPlex® ESI 16 System were obtained from 308 individuals. Allele frequencies were used to determine the relationships with other populations. Results: All loci were highly polymorphic and no significant deviation from HWE was detected. Allele frequencies showed that the samples of Aurès region share genetic affinities with other Algerian, North African and Middle Eastern samples, with the exception of samples from Iran and Matmata. Conclusions: These markers revealed a genetic homogeneity between the Algerian and North African samples. The genetic affinities indicate that this sample could share a common ancestor with the Middle Eastern samples.